Does Islamic Religiosity Influence Female Muslim Fashion Trend Purchase Intention? An Extended of Theory of Planned Behavior - Sulis Riptiono (Iqtishadia: Jurnal Kajian Ekonomi dan Bisnis Islam, 2019)
In this article we examine the effect of the variable Islamic Religiosity toward consumer purchase intention on Muslim fashion trends by using the extended of theory of planned behavior as the grand of the theory. Respondents in this study were female Muslim in Central Java, Indonesia. Data collected using purposive sampling and analysis tool used in this study is path analysis. The results showed that all hypotheses were accepted except hypotheses three. Subjective norms have the most influence on the intention to buy female Muslim fashion trends. Subjective norm variables have a significant effect on consumer attitudes and consumer purchase intentions on female Muslim fashion trends. Other findings state that the variable of Islamic religiosity does not have a significant effect on female Muslim purchase intention directly, but the Islamic religiosity variable indirectly influence toward female Muslim purchase intentions through consumer attitudes variables. Whereas for Perceived behavioral control variables have a positive effect on consumer purchase intention.Keyword: Islamic Religiosity, Theory of Planned Behavior, Female Muslim Fashion Trend, Purchase Intention